Eucalyptus Extrusion Injury: not such an Essential Oil?. (2nd March 2020) - Mustufvi, Zhain; Veale, Benjamin; Tkacz, Karolina; Adams, Aidan; Al-Khayyat, Ahmed
Abstract : Eucalyptus oil is an essential oil commonly used as a solvent to remove old gutta-percha when performing endodontic re-treatment procedures. Although commonly used by dentists, evidence for its safety is lacking. This report outlines a previously undocumented case of a 44-year-old male who attended the Oral and Maxillofacial Surgery department with sudden onset facial swelling in response to extrusion of eucalyptus oil through the apex of a tooth during root canal re-treatment by his dentist. The management of this case is discussed and the important safety aspects with regard to the chemicals used in endodontic treatments are reviewed. CPD/Clinical Relevance: This paper highlights that the risk of extrusion injury during endodontic treatment is not limited to the use of sodium hypochlorite but also to other chemicals such as, and in our case, eucalyptus oil.